Preference-based segmentation: A study of dish preferences among Vietnamese teenagers - Vu, Thi Hoa (University of Economics Ho Chi Minh City, 2023)
The purpose of this paper is to evaluate the usefulness of prefer-ence-based segmentation in understanding food-related behavior among Vietnamese teenagers. A sample of 413 teenagers in second-ary and high schools in three different regions is used. Their prefer-ences for 36 common Vietnamese dishes are evaluated. Four seg-ments based on their preferences are identified, including food likers (29%), poultry dislikers (27%), seafood dislikers (19%), and pork dislikers (25%). Differences between segments are profiled by a di-verse set of variables including consumption frequencies, food choice motives, attitudinal variables, and socio-demographic varia-bles. Dish preferences appear to be an appropriate basis for segmen-tation of Vietnamese adolescents. The differences found across the clusters for the differentiating variables can provide the basis for developing marketing strategies to target different segments, and also theoretical and practical implications are accordingly discussed.